The Effect of Nutrition Education on Knowledge, Attitudes and Consumption Patterns of Young Women in Prevention of Chronic Energy Deficiency in Bengkulu City - Kamsiah Kamsiah; Emy Yuliantini; Eliana Eliana; Rachmawati Rachmawati (Media Gizi Indonesia, 2023)
Adolescents is one of age groups vulnerable to nutritional status. Adolescence requires higher nutrition in order to optimize physical, cognitive and psychosocial growth. Lifestyle and diet of adolescents will affect the fulfillment of nutritional needs. Nutrition education can be carried out properly and can be received directly depending on how the message is conveyed, how the message is received and where the message is delivered. Barriers to prevention of chronic energy deficiency in adolescents can be sourced from environmental influences. Several studies The existence of significant changes in behavior in eating patterns through interventions from nutrition education can prevent Chronic Energy Deficiency (CED) in adolescents. This research aims to evaluate the impact of nutrition education on knowledge, attitudes and consumption patterns in prevention of CED in Young Girls SMPN 19 Padang Serai and SMKS Kampung Bahari, Bengkulu City. This study used quasi experiment with a two-group pre-test and post-test design. Â The intervention was carried out in the form of nutrition counseling using booklets or modules with a frequency of 3 meetings in 3 weeks. Nutrition education is promoting nutrition messages through education with a learning process using booklets individually and in groups using the lecture method. This study resulted an increased in knowledge, attitudes and consumption patterns after being given nutrition education in prevention of chronic energy deficiency of young women in Bengkulu City (p=0.000). There is an increase and influence between knowledge, attitudes and consumption patterns after being given adolescent nutrition education.